2016
DOI: 10.1002/aenm.201601950
|View full text |Cite
|
Sign up to set email alerts
|

Lattice‐Cell Orientation Disorder in Complex Spinel Oxides

Abstract: Transition metal (TM) substitution has been widely applied to change complex oxides crystal structures to create high energy density electrodes materials in high performance rechargeable lithium-ion batteries. The complex local structure in the oxides imparted by the TM arrangement often impacts their electrochemical behaviors by influencing the diffusion and intercalation of lithium. Here, a major discrepancy is demonstrated between the global and local structures of the promising high energy density and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 64 publications
(105 reference statements)
5
23
0
Order By: Relevance
“…S1, † (111) peak for pristine LNMO shis slightly to the high 2-theta, indicated that the decrease of intensity and lattice parameter of the LiNi 0.5 Mn 1.5 O 4 electrode without PEDOT. [47][48][49][50] But there is no evident of diffraction peaks shi of the cycled LNMO electrode with PEDOT coating. The diffraction peak shi for the electrode cycled in pristine LNMO is most likely caused by the dissolution of Mn 3+ from the bulk structure, which leads to generate the smaller radius of Mn 4+ via the disproportionation reaction.…”
Section: Resultsmentioning
confidence: 98%
“…S1, † (111) peak for pristine LNMO shis slightly to the high 2-theta, indicated that the decrease of intensity and lattice parameter of the LiNi 0.5 Mn 1.5 O 4 electrode without PEDOT. [47][48][49][50] But there is no evident of diffraction peaks shi of the cycled LNMO electrode with PEDOT coating. The diffraction peak shi for the electrode cycled in pristine LNMO is most likely caused by the dissolution of Mn 3+ from the bulk structure, which leads to generate the smaller radius of Mn 4+ via the disproportionation reaction.…”
Section: Resultsmentioning
confidence: 98%
“…[53][54][55][56] For long term annealing at 700 °C, LiMn 1.5 Ni 0.5 O 4 intended to become ordered structure, and the ordered structure is disturbed upon further higher heating. 57,58 While these samples were annealed at 800 °C and cooled down quickly, both of them retained the fully disordered structure. Both patterns of undoped and doped specimens did not show any superstructure peaks arising from ordered structure (P4 3 32 space group) and both were successfully refined according to the Fd 3 m space group of a disordered structure; the corresponding reliable factors R wp and R p are 3.76% and 2.89 % for the undoped specimen, and they were 3.36% and 2.47% for the doped specimen.…”
Section: Surface and Bulk Mn 3+ Concentrations Xps Characterization mentioning
confidence: 99%
“…The large cross-section of all components in the material make it possible to differentiate mixed phases and to monitor the phase evolutions under the external stimuli [33][34][35][36]. The static neutron incident slits and detectors of the TOF diffractometer ensure the high resolution to precisely resolve the lattice parameters/strains [37,38]. The average structure information given from a bulk provide statistical quantities such as phase fraction [39], preferential orientation [40], lattice site occupancy [41,42] and their evolutions [43,44].…”
Section: Introductionmentioning
confidence: 99%